Nurses’ role in the implementation of emerging Technologies in the management of chronic diseases: An integrative review (Research, Society and Development, 2025)
The study aimed to analyze the role of nurses in the implementation of emerging technologies in the management of chronic diseases, through an integrative literature review. Studies published between 2022 and 2025 were selected, which addressed the role of nurses in the integration of technologies such as artificial intelligence (AI), telemedicine, and wearable devices in the care of patients with cardiovascular diseases (CVDs). The analysis showed that these technologies promote accurate diagnoses, personalized treatments, and continuous monitoring, but face challenges such as lack of interoperability, disparity in access, and resistance to adoption. Strategies such as public-private partnerships, continuous capacity building, and expansion of telemedicine have been proposed to overcome these obstacles. The nurse acts as a mediator between technology, patient, and multiprofessional team, integrating data, validating AI alerts, and educating patients on the proper use of digital tools. Despite the advances, ethical and technical challenges persist, such as algorithmic bias and data privacy, which require regulation and auditing of algorithms. It is concluded that the effective implementation of these technologies depends on a collective effort, with investments in training, interoperability of systems and equity policies, ensuring more efficient and patient-centered care.